Aggressive Waves in the Lemon-Clawed Fiddler Crab (Uca perplexa): A Regional "Dialect" in Fiji. (14th May 2013) - Weis, Judith S.; Weis, Peddrick
Abstract : A population of the lemon-clawed fiddler crab ( U. perplexa ) in Fiji (island of Vanua Levu) was studied for types of communication (i.e., signaling via waving the male's larger claw). Two types of signals were observed. In addition to the expected territorial display of a large and complex vertical wave that conveys its message over a typical distance of 10–40 cm (with large males signaling to other large males over the greatest distance), a short, rapid, and horizontal wave was typically directed over a much shorter distance, rarely exceeding 10 cm. This latter wave type, seemingly of an aggressive nature, differs from the vertically directed aggressive signal observed in an Australian population of this species and thus appears to be a regional "dialect" for this mode of communication.